Living Lab Participants’ Knowledge Change about Inclusive Smart Cities: An Urban Living Lab in Seongdaegol, Seoul, South Korea - Jooho Park; Sayaka Fujii (Smart Cities, 2022)
The emergence of smart cities has illuminated positive expectations, such as the solving of urban problems through information and communications technology (ICT). Behind the spotlight of the smart city, not everybody is enjoying the smart infrastructure owing to knowledge gaps such as the digital divide. Living labs provide a new platform for smart cities that can prevent the failure of urban development. They give citizens a better understanding of how to adapt to life in a smart city, enabling the development of smart cities that are more likely to succeed through a participatory approach. In this way, the competencies of participants may affect the success of a living lab. Nevertheless, there is a lack of research on improving participants’ knowledge through living labs. This study aims to examine how participation in an urban living lab influences the knowledge level of photovoltaic power generation and to identify the influencing factors. Our empirical study shows that the knowledge level of solar power technology improved through participation in a living lab. Additionally, the results indicate that the types of activity programs in the living lab were not associated with knowledge acquisition.